Disparities in Dysphagia Care Among Head and Neck Cancer Patients: A Retrospective Cohort Study - Daniel Karasik; Gillian Michaelson; Claudia I. Cabrera; Alexis Nahra; Nina W. Zhao (OTO Open)
Abstract Objective To investigate the incidence of dysphagia among head and neck cancer (HNC) patients and assess disparities in utilization of speech‐language pathology (SLP) services across different demographic groups. Study Design Retrospective cohort study. Setting Analysis of data from the TriNetX global health network, comprising over 125 million deidentified electronic health records worldwide. Methods HNC patients diagnosed with oral, oropharyngeal, laryngeal, or nasopharyngeal cancer with and without dysphagia between January 1, 2004 and October 30, 2024 were identified. Patients were divided into two cohorts for comparison: those who received SLP services after dysphagia diagnosis and those who did not. The association of demographic characteristics (sex, ethnicity, and race) with SLP services were analyzed. Results Of 269,629 HNC patients, 28.8% (n = 77,562) were diagnosed with dysphagia. Significant disparities were found: female and non‐White patients were less likely to be diagnosed with dysphagia. Once diagnosed, female, Hispanic/Latino, and non‐White patients were also significantly less likely to receive SLP services compared to female, Hispanic/Latino, and non‐White patients. Overall, only 38.8% of patients with dysphagia received SLP services. Conclusion This study highlights significant sex, ethnic, and racial disparities in dysphagia diagnosis and SLP service utilization among HNC patients. Furthermore, SLP services are underutilized. There is a need for targeted interventions to increase dysphagia prevention and surveillance and ensure equitable access to dysphagia care, improving outcomes for all HNC survivors.